The rainbow comes and goes : a mother and son talk about life, love, and loss - Cooper, Anderson; Vanderbilt, Gloria, 1924-2019- (Harper, an imprint of HarperCollinsPublishers, 2016)
"A charming, intimate and fascinating collection of correspondence between broadcaster and #1 New York Times bestselling author Anderson Cooper and his mother, the celebrated Gloria Vanderbilt"--